A Study on the Interaction Between Steroids and Proteins - SINGH, R.P.; TOMER, A.S.; ARORA, S.K.; CHAUDHARY, ROMY (Asian Journal of Chemistry, 2010)
The binding of cholesterol and its stearate ester was studied with soluble ovalbumin and Transfusion gelatin using partition and dialysis equilibrium methods. The intrinsic association constants and binding sites were found to be pH and temperature dependent. The linear nature of binding plots suggests the involvement of single one class of sites in the interaction. The binding was found to be maximum in the physiological pH range while lesser at pH 11.5, which was ascribed to protein denaturation. Approximately similar values of log K at all pH values suggested the involment of identical sites in steroid-protein interaction.